Genetic- and fiber-diet-mediated changes in virulence factors in pig colon contents and feces and their driving factors - Wang, Tao; Luo, Yuheng; Kong, Xiangfeng; Yu, Bing; Zheng, Ping; Huang, Zhiqing; Mao, Xiangbing; Yu, Jie; Luo, Junqiu; Yan, Hui; He, Jun (Frontiers in Veterinary Science, 2024)
Virulence factors (VFs) are key factors for microorganisms to establish defense mechanisms in the host and enhance their pathogenic potential. However, the spectrum of virulence factors in pig colon and feces, as well as the influence of dietary and genetic factors on them, remains unreported. In this study, we firstly revealed the diversity, abundance and distribution characteristics of VFs in the colonic contents of different breeds of pigs (Taoyuan, Xiangcun and Duroc pig) fed with different fiber levels by using a metagenomic analysis. The analysis resulted in the identification of 1,236 virulence factors, which could be grouped into 16 virulence features. Among these, Taoyuan pigs exhibited significantly higher levels of virulence factors compared to Duroc pigs. The high-fiber diet significantly reduced the abundance of certain virulence factor categories, including iron uptake systems (FbpABC, HitABC) and Ig protease categories in the colon, along with a noteworthy decrease in the relative abundance of plasmid categories in mobile genetic elements (MGEs). Further we examined VFs in feces using absolute quantification. The results showed that high-fiber diets reduce fecal excretion of VFs and that this effect is strongly influenced by MGEs and short-chain fatty acids (SCFAs). In vitro fermentation experiments confirmed that acetic acid (AA) led to a decrease in the relative abundance of VFs (p < 0.1). In conclusion, our findings reveal for the first time how fiber diet and genetic factors affect the distribution of VFs in pig colon contents and feces and their driving factors. This information provides valuable reference data to further improve food safety and animal health.